A simplified and optimized protocol for total DNA extraction from insect species: applicable for studying genetic diversity and PCR-based specimen identification via partial amplification of cytochrome oxidase I (COI) gene - Paydar, Samira; Ucar, Esra; Yari, Peyman; Safavi, Seyed Mehdi; Kahrizi, Danial; Nateqi, Masoud; Mirmoayedi, Alinaghi; Yari, Kheirollah (Cellular and Molecular Biology, 2018)
The efficient DNA extraction from insects has been suggested as a critical and main step affecting molecular entomology for taxonomic identification, the establishment of DNA barcoding library and analysis of genetic diversity relationship between insect populations. For successfully apply these molecular techniques, high-quantity and high-quality of the extracted DNA are required. Several protocols for efficient genomic DNA extraction from insects have been developed. In this research, we represent a rapid, reliable and cost-effective method that it is not reliant on poisonous and enzymatic reagents for DNA extraction from insect tissues. Results showed that high quantity and high-quality of the isolated DNA by this method is suitable and can be used directly for PCR, also is enough to do hundreds of molecular reactions. In conclusion, we described a fast, cost-effective, non-toxic and enzyme-free protocol for high yield genomic DNA extraction from green Lacewings (Chrysoperla carnea) tissues in basic equipment laboratories.